Tumor necrosis factor-like weak inducer of apoptosis-induced neurodegeneration - Inta, Ioana; Zhang, Wen; Burkly, Linda; Hahm, Kyungmin; Lincecum, John; Wang, Monica Z.; Maurer, Martin H.; Roßner, Moritz; Schneider, Armin; Schwaninger, Markus (The journal of neuroscience, 2004)
Tumor necrosis factor-like weak inducer of apoptosis (TWEAK) is a member of the tumor necrosis factor (TNF) family of cytokines. It has proangiogenic and proinflammatory properties in vivo and induces cell death in tumor cell lines. TWEAK effects are mediated by the membrane receptor Fn14. In a systematic search for genes regulated in a murine stroke model with the tag-sequencing technique massively parallel signature sequencing, we have identified TWEAK as an induced gene. After 24 hr of focal cerebral ischemia in vivo or oxygen glucose deprivation in primary cortical neurons, both TWEAK and its receptor Fn14 were significantly upregulated. TWEAK induced cell death in primary neurons. Transfection of a nuclear factor (NF)-κB-luciferase fusion gene demonstrated that TWEAK stimulated transcriptional activity of NF-κB through Fn14 and the IκB kinase. Inhibition of NF-κB reduced TWEAK-stimulated neuronal cell death, suggesting that NF-κB mediates TWEAK-induced neurodegeneration at least in part. Intraperitoneal injection of a neutralizing anti-TWEAK antibody significantly reduced the infarct size after 48 hr of permanent cerebral ischemia. In summary, our data show that TWEAK induces neuronal cell death and is involved in neurodegeneration in vivo.
Gesehen am 02.06.2021